2007
DOI: 10.1002/sim.2798
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐aided diagnosis with potential application to rapid detection of disease outbreaks

Abstract: Our objectives are to quickly interpret symptoms of emergency patients to identify likely syndromes and to improve population-wide disease outbreak detection. We constructed a database of 248 syndromes, each syndrome having an estimated probability of producing any of 85 symptoms, with some two-way, three-way, and five-way probabilities reflecting correlations among symptoms. Using these multi-way probabilities in conjunction with an iterative proportional fitting algorithm allows estimation of full conditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Anecdotal evidence suggests the need to reason quantitatively.To a certain extent the approach is similar to what one might envision, for example, in recognizing unnatural disease outbreaks or in modern quality control applications. In monitoring for unnatural disease outbreaks (Burr et al 2007) one must use observed patient symptoms that are measured with error, account for the background incidence of possible diseases (the "prior" probability of each candidate disease), and somehow aggregate estimated probabilities of candidate diseases by patient over space and time. Burr et al (2007) allowed the user to vary the prior disease probability for the same reason our safeguards sliders are provided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anecdotal evidence suggests the need to reason quantitatively.To a certain extent the approach is similar to what one might envision, for example, in recognizing unnatural disease outbreaks or in modern quality control applications. In monitoring for unnatural disease outbreaks (Burr et al 2007) one must use observed patient symptoms that are measured with error, account for the background incidence of possible diseases (the "prior" probability of each candidate disease), and somehow aggregate estimated probabilities of candidate diseases by patient over space and time. Burr et al (2007) allowed the user to vary the prior disease probability for the same reason our safeguards sliders are provided.…”
Section: Discussionmentioning
confidence: 99%
“…In monitoring for unnatural disease outbreaks (Burr et al 2007) one must use observed patient symptoms that are measured with error, account for the background incidence of possible diseases (the "prior" probability of each candidate disease), and somehow aggregate estimated probabilities of candidate diseases by patient over space and time. Burr et al (2007) allowed the user to vary the prior disease probability for the same reason our safeguards sliders are provided. In modern quality control, described for example in (Hines et al, 2007), there is a need to monitor both for product quality drift and for instrument calibration drift, so the task of learning normal behaviour is challenging for reasons that are similar to the reasons it is challenging to learn normal behaviour in our described safeguards application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the problem of missing values challenges reliable data analysis. It is important to determine whether the unrecorded positive status of a symptom means that the status was negative or that the status was unknown . Because the missing patterns of clinical data are highly relevant to different TCM physicians, this indicates that physician name or code should be included as one of the essential fields in TCM clinical data, which would be valuable for data analysis.…”
Section: Challenges Of Tcm Clinical Data Processing and Analysismentioning
confidence: 99%